Everyday challenges to women’s presence and authority yield greater burnout and less persistence in a male-dominated profession - Melissa J. Williams; Brandon Esianor; Sara Hendrick; Janice L. Farlow; Annie Farrell; Robbi A. Kupfer; Tanya K. Meyer; Kimberly N. Vinson; Grace M. Wandell; Amy Y. Chen (Proceedings of the National Academy of Sciences, 2025)
While most people believe that women (vs. men) experience more discriminatory treatment at work, especially in male-dominated professions, relatively few women report experiencing such treatment themselves. These low levels of reporting may arise either because discriminatory treatment has declined, even while laypeople’s assumptions of widespread discrimination persist, or because it is difficult for individuals to know when they are experiencing discriminatory treatment, leading to underreporting. In investigating this puzzle, we theorized four types of nonsexual workplace experiences that may target women and accumulate to harm well-being, yet may be difficult to recognize as discrimination. To test our predictions, we conducted a longitudinal, multisite experience-sampling study of surgeons, capturing workplace experiences over 5 mo. This approach addresses methodological limitations of past research, which include recall biases, demand characteristics, and low external validity. Consistent with hypotheses, female (vs. male) surgeons had more experiences in which their role was challenged or their authority questioned. Moreover, the frequency and severity of these experiences predicted increased burnout over time and decreased intentions to persist in surgery, regardless of whether participants attributed their experiences to their gender. Contrary to hypotheses, female surgeons did not encounter more presumptions of their helpfulness. Female surgeons also received more positive feedback, especially from other women, which yielded increases in professional efficacy and intentions to persist in surgery. Thus, while difficult to detect, workplace discriminatory treatment continues to harm women’s well-being and career opportunities, impede organizations’ efforts to recruit and retain women professionals, and exacerbate burnout among health care providers.